Endocrinopathies in Survivors of Childhood Neoplasia - Barnes, Nicole; Chemaitilly, Wassim (Frontiers in Pediatrics, 2014)
Advancements in cancer treatments have increased the number of childhood cancer survivors. Endocrinopathies are common complications following cancer therapy and may occur decades later. The objective of the review is to address the main endocrine abnormalities detected in childhood cancer survivors including disorders of the hypothalamic-pituitary axis, thyroid, puberty, gonads, bone, body composition, and glucose metabolism.